BEYOND POVERTY AND PATRIARCHY: WOMEN’S EDUCATION AS CATALYST FOR ECONOMIC AGENCY AND FAMILY EMPOWERMENT IN RURAL LAMPUNG - Nugroho, Dwi; Setyawan, Dharma (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Many women do not continue their education due to patriarchal paradigms within their families and society, as well as economic constraints. However, higher education is a space for women to actualize themselves, improve their competencies, and strengthen their relationships in order to face future challenges. This study aims to observe and investigate how women fight for their educational rights and apply their knowledge in various situations. This study focuses on the perspectives of young women and parents in Liman Benawi as primary data. The results of this study indicate that first, women's persistence in communicating and negotiating with parents about education and the future serves as an effort to raise parents' awareness of the positive impacts of education. Second, those from disadvantaged families must take on the consequences of working part-time or seeking scholarships. Third, educated women ultimately have many opportunities to secure employment, activate family education for their children, and bring about social-cultural and socio-economic impacts. Therefore, to reduce pressure on others rural women, affirmative policies such as special scholarships for rural women from poor families are needed as a means of reducing financial barriers. Additionally, mentoring programs involving successful women from diverse backgrounds can serve as both inspiration and role models in fostering educational aspirations. Integrating a gender equality perspective into village development planning can also be a long-term strategy for transforming the deeply rooted social and cultural structures that perpetuate gender bias.